Lipoma of the Palate: An Uncommon Finding - Volpato, Luiz Evaristo Ricci (Open Dent J, 2016)
BACKGROUND: Lipoma is a benign neoplasm originated from adipose cells circumscribed by connective tissue. This neoplasm represents about 1% to 4.4% of all oral benign tumors and it is rarely located in the palate area. OBJECTIVE: This case reports the occurrence of an oral lipoma in the hard palate of a 57-year-old woman and discusses its etiology and treatment. CASE REPORT: The treatment consisted in the total resection of the lesion and laser therapy. The patient is being followed up for forty three months with no signs of recurrence. CONCLUSION: Lipoma in hard palate is a rare entity that may be associated with endocrine factors and local inflammation.